Evaluation of Phyllanthus niruri L. from Malaysia for In-vitro Anti-Urolithiatic properties by different solvent extraction - Gul, Muhammad Tayyab; Muhammad, Norhayati; Pauzi, Aslia Natasha; Abu Bakar, Mohd Fadzelly; A. Talip, Balkis; Abdullah, Norazlin; Abdul Rahim, Nur Fazira; Syukriah, Wan Nur Ain; Marzuki, Wan; B. Din, Laily; Ibrahime, Nazlina (2021)
The Phyllanthus niruri is traditionally used for curing of kidney disorders and urinary stones in Malaysia. Hence the current work was aimed to evaluate the effect of different solvents extract (n- hexane, ethyl acetate, methanol and water) of P. niruri for in vitro anti-urolithiatic properties in terms of inhibition activity on CaOx by using the rate of CaOx aggregation assay and dissolution of calcium oxalate (CaOx) crystal by using titrimetry method. Cystone was used as positive control. The effects of cystone on slope of nucleation and aggregation as well as growth of CaOx were evaluated spectrophotometrically. The highest yield percentage of P.niruri was occupied by methanol (5.74 %). The maximum inhibition against aggregation of CaOx crystals was also occupied by methanol (66.67 % ± 1.61) and was comprised with alkaloid, steroid, terpenoid and tannin. Dissolution effect on calcium oxalate crystals indicates that the aqueous extracts of P. niruri was found to be more effective in dissolution of CaOx with 63.33 % ± 1.44. P. niruri significantly (P < 0.05) inhibited the slope of nucleation and aggregation of CaOx crystallization, and reduced the crystal density. The results of the present study confirmed that P. niruri leaves can be used as remedial mediator for urolithiasis. However, further studies are required for isolation and identification of active constituents and their in-vivo confirmation.